(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
The objective of the study was to evaluate the effects of an intervention, aimed at promoting the development of children with autism and carried out by the training of caregivers of these children, in a school clinic accredited by the Unified Health System. Participating in the study of four children as a medical diagnosis of Autism Spectrum Disorders, their caregivers and seven academics of the psychology course, which were in mandatory supervised practice. The children were tested at the beginning and at the end of the intervention and the results indicated gains in their development. The results of this study may be important to expand research into the treatment of Autism Spectrum Disorders in the scope of the Unified Health System.